Antibody Subclass and Glycosylation Shift Following Effective TB Treatment - Grace, Patricia S.; Dolatshahi, Sepideh; Lu, Lenette L.; Cain, Adam; Palmieri, Fabrizio; Petrone, Linda; Fortune, Sarah M.; Ottenhoff, Tom H. M.; Lauffenburger, Douglas A.; Goletti, Delia; Joosten, Simone A.; Alter, Galit (Frontiers in Immunology, 2021)
With an estimated 25% of the global population infected with Mycobacterium tuberculosis (Mtb), tuberculosis (TB) remains a leading cause of death by infectious diseases. Humoral immunity following TB treatment is largely uncharacterized, and antibody profiling could provide insights into disease resolution. Here we focused on the distinctive TB-specific serum antibody features in active TB disease (ATB) and compared them with latent TB infection (LTBI) or treated ATB (txATB). As expected, di-galactosylated glycan structures (lacking sialic acid) found on IgG-Fc differentiated LTBI from ATB, but also discriminated txATB from ATB. Moreover, TB-specific IgG4 emerged as a novel antibody feature that correlated with active disease; elevated in ATB, but significantly diminished after therapy. These findings highlight 2 novel TB-specific antibody changes that track with the resolution of TB and may provide key insights to guide TB therapy.